Introducing physical geography - Strahler, Alan H. (Hoboken, NJ : Wiley, 2013)
Overview: The 6th edition of Introducing Physical Geography is known for its clear writing, distinctive photos and illustrations and a strong supplements program. The text continues its tradition as a great book to help non-science readers visualize and understand earth processes and learn the basic language of physical geography. The new edition features a strengthened "Eye on Global Change" coverage and coverage of the geographer's tool box.
Earth materials And Plate Tectonics: -- Changing Earth: -- Timescale for geologic change -- Forces of geologic change -- Structure of the earth: -- Core -- Mantle -- Crust and lithosphere -- Earth materials and the cycle of rock change: -- Igneous rocks -- Sediments and sedimentary rocks -- Metamorphic rocks -- Cycle of rock change -- Global topography: -- Relief features of the continents -- Focus on remote sensing: -- Mapping the earth's topography from space -- Relief features of the ocean basins -- Configuration of the continents -- Plate tectonics: -- Extension and compression -- Plates and boundaries -- Continental rupture and new ocean basins -- Island arcs and collision of oceanic lithospheric plates -- ARC-continent collision -- Continent-continent collision -- Wilson cycle and supercontinents -- Power source for plate movements -- Look ahead: -- Tectonic And Volcanic Landforms: -- Eye on global change: the great Tohoku earthquake of 2011: -- Tectonic landforms: -- Rock structures of converging boundaries -- Plate interiors -- Coastal plains -- Faults and fault landforms -- Earthquakes: -- Epicenter and focus -- Magnitude -- Tectonic environments of earthquakes -- Subduction-zone earthquakes -- Transform boundaries -- Volcanic activity and landforms: -- Tectonic environments of volcanoes -- Volcanic eruptions -- Types of volcanoes -- Focus on remote sensing: -- Remote sensing of volcanoes -- Hot springs, geysers, and geothermal power -- Look ahead: -- Weathering And Mass Wasting: -- Eye on global change: the Madison slide: -- Weathering: -- Physical weathering -- Chemical weathering -- Slopes and slope processes -- Slopes -- Slope stability -- Mass wasting: -- Creep -- Rockfalls and talus -- Slides -- Flows -- Induced mass wasting -- Look ahead: -- Freshwater Of The Continents: -- Eye on global change: the Aral sea: -- Freshwater and the hydrologic cycle -- Paths of precipitation -- Groundwater: -- Water table -- Aquifers -- Limestone solution by groundwater -- Groundwater use and management: -- Groundwater withdrawal subsidence -- Pollution of groundwater -- Surface water and streamflow: -- Overland flow -- Drainage systems -- Stream channels and discharge -- Flooding: -- Floodplains -- Flood profiles -- Urbanization and streamflow -- Lakes: -- Great Lakes -- Saline lakes and salt flats -- Desert irrigation -- Freshwater as a natural resource: -- Water access and supply -- Pollution of surface water -- Look ahead: -- Landforms Made By Running Water: -- Erosion, transportation, and deposition: -- Slope erosion -- Sediment yield -- Stream erosion -- Stream transportation -- Deposition -- Stream gradation and evolution: -- Stream gradation -- Evolution of stream valleys -- Focus on remote sensing: -- Canyons from space -- Stream rejuvenation -- Theories of landscape evolution -- Fluvial landforms: -- Meandering streams and floodplains braided streams -- Deltas -- Fluvial processes in a Arid climate: -- Alluvial fans -- Mountainous deserts -- Look ahead: -- Landforms Made By Waves And Wind: -- Eye on global change: global change and coastal environments: -- Work of waves and tides: -- Waves -- Littoral drift -- Wave refraction -- Tides -- Tsunamis -- Coastal landforms: -- Erosional coastal landforms -- Depositional coastal landforms -- Coastlines of submergence -- Coral reefs -- Coastal engineering -- Wind action: -- Erosion by wind -- Transportation by wind -- Eolian landforms: -- Sand dunes -- Types of dunes -- Loess -- Look ahead: -- Glacial And Periglacial Landforms: -- Eye on global change: ice sheets, sea ice, and global warming: -- Types of glaciers: -- Alpine glaciers -- Ice sheets -- Ice shelves, sea ice, and icebergs -- Glacial processes: -- Formation of glaciers -- Movement of glaciers -- Glacial erosion and deposition -- Glacial landforms: -- Landforms made by alpine glaciers -- Focus on remote sensing: -- Remote sensing of glaciers -- Landforms made by ice sheets -- Human use of glacial landforms -- Periglacial processes and landforms: -- Permafrost -- Ground ice and periglacial landforms -- Human interactions with periglacial environments -- Global climate and glaciation: -- History of glaciation -- Holocene epoch -- Triggering the ice age -- Cycles of glaciation -- Glaciation and global warming -- Look ahead: -- Appendix 1: Climate definitions and boundaries -- Appendix 2: Conversion factors -- Appendix 3: Topographic map symbols -- Glossary -- Illustration credits -- Index.
Includes index.
Keywords: Physical geography